Magnetic penetration depth determination of the high Tc superconductor YBa2Cu3O7 by polarized neutron reflection - Felici, R; Matacotta, F; Olzi, E; Penfold, J; Ward, R (1988)
The magnetic penetration depth, Λ, is one of the characteristic quantities of a superconductor because it is strictly related to the density of superconducting electrons. The absolute determination of the magnetic penetration depth is possible by using polarized neutron reflection. We have used this technique to determine Λ in the YBa2Cu3O7 high Tc superconductor obtaining a value of 225±75 angstrom at a temperature of 5.0 K.